Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1073/pnas.1807027115
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic iron-carbene intermediate revealed in a cytochrome c carbene transferase

Abstract: Recently, heme proteins have been discovered and engineered by directed evolution to catalyze chemical transformations that are biochemically unprecedented. Many of these nonnatural enzyme-catalyzed reactions are assumed to proceed through a catalytic iron porphyrin carbene (IPC) intermediate, although this intermediate has never been observed in a protein. Using crystallographic, spectroscopic, and computational methods, we have captured and studied a catalytic IPC intermediate in the active site of an enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
151
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 106 publications
(176 citation statements)
references
References 60 publications
23
151
1
1
Order By: Relevance
“…Given these data, we assign the new spectroscopically distinct species we describe above to the C45 and Rma-TDE metallocarbenoid intermediates. It should be noted that at this time we cannot definitively assign these spectra as either the non-bridging metallocarbenoid species observed by Lewis et al 45 or the porphyrin-bridging species observed by Hayashi et al 48 in the crystal structures of engineered cytochrome c or N-methylhistidine-ligated myoglobin variant (Mb(H64V,V68A)) respectively. However, given the identical nature of the C45 and Rma-TDE spectra, it would seem likely that the spectra obtained represent the non-bridging ligation observed in the Rma-TDE Me-EDA crystal structure 45 .…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…Given these data, we assign the new spectroscopically distinct species we describe above to the C45 and Rma-TDE metallocarbenoid intermediates. It should be noted that at this time we cannot definitively assign these spectra as either the non-bridging metallocarbenoid species observed by Lewis et al 45 or the porphyrin-bridging species observed by Hayashi et al 48 in the crystal structures of engineered cytochrome c or N-methylhistidine-ligated myoglobin variant (Mb(H64V,V68A)) respectively. However, given the identical nature of the C45 and Rma-TDE spectra, it would seem likely that the spectra obtained represent the non-bridging ligation observed in the Rma-TDE Me-EDA crystal structure 45 .…”
Section: Resultsmentioning
confidence: 63%
“…It should be noted that at this time we cannot definitively assign these spectra as either the non-bridging metallocarbenoid species observed by Lewis et al 45 or the porphyrin-bridging species observed by Hayashi et al 48 in the crystal structures of engineered cytochrome c or N-methylhistidine-ligated myoglobin variant (Mb(H64V,V68A)) respectively. However, given the identical nature of the C45 and Rma-TDE spectra, it would seem likely that the spectra obtained represent the non-bridging ligation observed in the Rma-TDE Me-EDA crystal structure 45 . Additionally, while the rate of metallocarbenoid intermediate and subsequent product formation appear relatively low in our stopped-flow experiments, it is worth noting that the selected conditions were necessary for maximizing the quantity of intermediate in the stopped-flow apparatus, and that subsequent activity assays were carried out at higher substrate concentrations (both EDA and styrene), higher temperature and lower ethanol concentrations.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations